Interaction of Salmonella typhimurium with dendritic cells derived from pluripotent embryonic stem cells. - Raffaella Rossi; Christine Hale; David Goulding; Robert Andrews; Zarah Abdellah; Paul J Fairchild; Gordon Dougan (PLoS ONE)
Using an in vitro differentiation protocol we isolated cells with the properties of dendritic cells (DCs) from immunologically refractive pluripotent murine embryonic stem cells (ESCs). These ES-derived dendritic cells (ESDCs) expressed cytokines and were able to present antigen to a T cell line. Infection of ESDCs with Salmonella Typhimurium stimulated the expression of immune cell markers and thousands of murine genes, many associated with the immune response. Consequently, this system provides a novel in vitro model, amenable to genetic modification, for monitoring host/pathogen interactions.